Trends and challenges of developing human capital in Singapore: an analysis of current and future potentials - Osman-Gani, Aahad M.; Chan, Teng Heng (Taylor & Francis, 2009)
As one of the most vibrant nations of Asia, Singapore is well known for its dynamic and innovative human capital development initiatives. These are driven mainly by the government policies, with inputs from public sector organizations and large local companies. Human resource development (HRD) related legislations, financial incentives, infra-structural support and deployment of management and info-communication technologies (ICT) help to sustain the national HRD initiatives. This paper presents an analysis of the current practices and future trends and challenges faced by organizations in Singapore. Some of these challenges are: ageing workforce, talent retention and development, rapid technological changes and cross-cultural skills development for working in the emerging markets. Eight trends and challenges identified here are expected to significantly impact the HRD profession in future. Implications of the trends and challenges are also discussed for future research and professional practice.